Fossils in Rome: Searching for sources of information - Magagnini, Antonella (Journal of Mediterranean Earth Sciences, 2023)
A complex array of events, a plurality of characters, and a dense network of relationships have characterized the Roman scenario from an archeological, collecting, and museum perspective for at least four centuries. The wealth of information resulting from this is such that it allows for countless lines of research, based on the diverse characteristics of such a vast chronological span. Due to the different periods, it is indeed possible to aggregate data concerning the formation and dispersion of collections, the relationship with the contemporary public, the circulation of information, the origin and/or reorganization of museum collections, and the acquisition of information about the provenance of finds.